P258 Change in Sleep Study and CPAP Provision Following the NIHCE CPAP TA. (19th November 2012) - Hill, G; Stradling, JR
Abstract : Introduction: We have assessed whether Primary Care Trusts' (PCTs) commissioning of sleep services has improved following the NIHCE 2008 technology appraisal on CPAP. Methods: We wrote to all PCTs in England, (under the Freedom of Information Act, 2000) for information on sleep studies commissioned, and CPAP prescriptions issued, for the years ending 31 March, 2008, 09, and 10. The PCTs were also asked who provided sleep studies or CPAP on their behalf (NHS hospital, GP, private, or other provider). Some PCTs did not reply, or claimed not to hold data, so we contacted appropriate NHS hospitals to obtain further information. Sleep study data was only obtained from approximately 75% of PCTs or associated hospitals. An alternative set of data, on the Department of Health (DH) website, was also used. Limited sales data from CPAP companies was also available for comparison. Results: In almost all PCTs, sleep studies and CPAP provision were from NHS hospitals. The incomplete data from PCTs showed that sleep studies rose from about 30, 000 in 2007/8 to 48, 000 in 2009/10, a 3-year increase of about 60%. Data on sleep studies published by DH rose from over 61, 000 in 2007/8 to over 86, 000 in 2009/10, a 3-year increase of 41%. For CPAP prescriptions issued, only 66% of PCTs submitted data for 2007/8, rising to a 75% response by 2009/10. On the basis of this incomplete information and with some assumptions, annual CPAP prescriptions rose from less than 17, 000 in 2007/8 to over 37, 800 by 2009/10, a three year increase of 126%. There may be some under-reporting in the earlier years, and the industry sources suggested a 3-year lower increase of nearer 80%. In addition there are likely to be errors of coding. However, there was wide variation between PCTs suggesting patchy performance. Conclusions: We believe that the results show a clear improvement in the number of sleep studies and CPAP prescriptions over this period. Thus, following the NIHCE TA there has been an improvement in patient access to the diagnosis and treatment of sleep apnoea, though we are concerned that the wide variation suggests there is a substantial element of post-code lottery.